Professional fees in corporate bankruptcies data, analysis, and evaluation - LoPucki, Lynn M.; Doherty, Joseph W. (New York ; Oxford : Oxford University Press, 2011)
This title is based on a study of thousands of documents from the court files in over a hundred of the largest bankruptcy cases. It employs statistical analysis and documents its findings, and provides an unprecedented window on the worlds of bankruptcy professionals, professional fees, and their scientific study.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Bankruptcy -- United States -- Costs; Bankruptcy lawyers -- Fees -- United States; Corporate lawyers -- Fees -- United States